(untitled) (Journal of Sciences & Technology, 2020)
Polymers may replace advantageously the traditional materials of structure. We can distinguish among others their lightness, their moderate cost, their various processes which allow to implement and to shape them simultaneously. In the thermoplastic polymers case numerous are their peculiarities which make them interesting. The majority of studies of the thermoplastics and their composites become only attached to their mechanical properties; their behavior is more complex and establishes an obstacle major which requires more thorough studies. Our objective is the incorporation of a mineral filler the CaCO3 in the polyoxyméthylene (POM) in the context of the development of a new composite material and to define its thermals, physical and mechanicals properties. So,our work consists in studying the thermals, physical and mechanicals properties of the composite Polyoxymethylene / CaCO3.